Capital structure, profitability, hedging policy, firm size, and firm value: Mediation and moderation analysis - Alghifari, Erik Syawal; Solikin, Ikin; Nugraha, Nugraha; Waspada, Ika; Sari, Maya; Puspitawati , Lilis (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aims to ascertain how the capital structure affects firm value via profitability moderated by hedging practices and firm size. Verification analysis is used in this study, with data analysis techniques through conditional process analysis. Companies from miscellaneous industrial sectors that were listed on the Indonesia Stock Exchange between 2016 and 2020 make up the research population. The study showed that: capital structure affects profitability; capital structure and profitability affect firm value; profitability does not mediate the effect of capital structure on firm value, which is moderated by hedging policies and firm size; hedging policies and firm size do not moderate the indirect effect of profitability on firm value. This conclusion is crucial for decision-makers who aim to optimize the structure to raise the business value.